The Unemployment-Specialization Relationship under Collective Bargaining Constraints Evidence from EU Regions - Simonetta Longhi; Peter Nijkamp; Iulia Traistaru (European Regional Science Association (ERSA), 2004)
Standard labor market theories predict that workers employed in more specialized areas earn higher wages in comparison with similar workers employed in less specialized areas. Empirical studies for the US generally confirm the existence of a positive effect of sectoral specialization on wages and on unemployment. However, these relationships might not hold in labor markets that are characterized by substantially higher collective bargaining coverage and more centralized bargaining systems. In the EU, for example, collective wage agreements impose identical wages across regions belonging to the same country, thus leaving little room for regional wage flexibility. Using regional data for EU member states, we model regional unemployment as a function of regional specialization measures. The comparison between such countries, that are still characterized by separate and independent collective agreements on wages, can give us new insights on the effects that collective bargaining may have on the relationship between sectoral specialization of regions and regional unemployment rates.
Keywords: 330